Accessibility of facilities in hotel capacities for people with disabilities - Jević Goran; Jević Jelena (Turističko Poslovanje, 2015)
Given the fact that, only in Europe, there are over 80 million people, with some type of disability, and that these figures will be constantly on the increase according to the projections of World Health Organization, it implies that accessible tourism market, which is now unfortunately neglected, has great potential for future development. The term 'access' implies the absence of barriers in using facilities, and as such, perceived within the tourism and hospitality market mainly entails the accessibility of accommodation facilities for disabled persons. This paper aims at presenting and familiarizing with the term 'disability' as well as highlighting the importance of accessible tourism together with the need to adapt accommodation to people with disabilities. The methods used for data collection are based on the desk research with the use of national and foreign academic literature, primarily in the field of tourism and hospitality. For data processing we mostly relied on the methods of analysis, synthesis and comparison. The paper is organized as follows: the first part is entitled 'Definition and Models of Disability', the second part deals with 'Accessibility and Legislation', whereas the third part tackles 'Accessibility and Hospitality'. Based on the research findings, it can be concluded that disabled persons are faced with serious problems upon choosing and selecting a hotel, which is partly caused by the disrespect for their rights and the lack in adaptability of accommodation facilities as well as the lack of employees' awareness about the needs of people with disabilities.